Kemični motilci endokrinega sistema in reproduktivno zdravje žensk - Srnovršnik, Tinkara (Farmacevtski vestnik, 2023)
The endocrine disrupting chemicals (EDCs) are a heterogeneous group of chemicals that interfere with endocrine functions. Human exposure mainly occurs by ingestion of contaminated food and water. EDCs can bind to hormone receptors and interfere with steroidogenesis, sex-hormone metabolism and bioavailability. They have been linked to gynaecological disorders such as infertility, polycystic ovary syndrome, irregular menstrual cycle, endometriosis, fibroids or hormone-responsive cancers. Regarding their potential impact on female reproductive health, health care professionals should play a key role in communicating the science of EDCs to the general public, in particular to women of childbearing age.
Keywords: endokrini motilci; ginekološke bolezni; Hormonski motilci; neplodnost; Rak (medicina); steroidni hormoni